Perception of climate change and adaptation strategies in Vietnam: Are there intra-household gender differences? - Mishra, Ashok K.; Pede, Valerien O. (Emerald Publishing Limited, 2017)
Purpose: The purpose of this study is to first examine the factors affecting the intra-household perception of climate change. Second, the study investigates the impact of the perception of climatic stress on the operators’ and spouses’ intra-household adaptation strategies (farm and household financial strategies).